2017
DOI: 10.1111/ijfs.13516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vitro‐simulated gastrointestinal digestion on the stability and antioxidant activity of blueberry polyphenols and their cellular antioxidant activity towards HepG2 cells

Abstract: SummaryIn this study we investigated the influence of in vitro-simulated gastrointestinal digestion on the bioaccessibility and antioxidant activity of polyphenols from blueberries (Vaccinium spp.). Total phenolic, anthocyanin, and flavonoid content was determined, and extract and digesta compositions were analysed by HPLC-ESI-MS/MS. The phenolic compounds were relatively stable under a gastric environment, whereas polyphenols and anthocyanins were unstable under an intestinal environment. The bioaccessibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 54 publications
(71 reference statements)
4
53
1
Order By: Relevance
“…The net bioaccesibility (TP FC = oral + gastric + intestinal) of polyphenols (as mg GAE per g DW) from Red Globe grape, raspberry, and blackberry was 2.0, 3.6 and 4.2 (A t0 , Table 2) which represents 21.3, 20.4 and 18.6% of their original content [7]. In our preceding study we also reported that anthocyanins, but no other flavonoids were pH-unstable under simulated intestinal conditions (pH 7.0); similar results have been reported for strawberry [26], maqui berry [27] and blueberry [28]. After intestinal digestion (Table 2), 1.3, 1.5 and 2.4 mg GAE per g DW remain in the apical side (A t120 ) suggesting 35%, 58% and, 43% of net polyphenol absorption; however, the basolateral (serosal) concentration of polyphenols at 2h (B t120 ) was blackberry (0.13) > Red Globe grape/ raspberry (~0.095) and the absorptive (A t120 →B t120 ) and secretory (B t120 →A t120 ) P app (cm•s −1 × 10 −5 ) were Red Globe grape (1.20)> blackberry (0.06)/ raspberry (0.07) and Red Globe grape (1.55)/blackberry (1.38) > raspberry (0.98), respectively.…”
Section: Apparent Permeability Of Berry Polyphenolssupporting
confidence: 80%
See 2 more Smart Citations
“…The net bioaccesibility (TP FC = oral + gastric + intestinal) of polyphenols (as mg GAE per g DW) from Red Globe grape, raspberry, and blackberry was 2.0, 3.6 and 4.2 (A t0 , Table 2) which represents 21.3, 20.4 and 18.6% of their original content [7]. In our preceding study we also reported that anthocyanins, but no other flavonoids were pH-unstable under simulated intestinal conditions (pH 7.0); similar results have been reported for strawberry [26], maqui berry [27] and blueberry [28]. After intestinal digestion (Table 2), 1.3, 1.5 and 2.4 mg GAE per g DW remain in the apical side (A t120 ) suggesting 35%, 58% and, 43% of net polyphenol absorption; however, the basolateral (serosal) concentration of polyphenols at 2h (B t120 ) was blackberry (0.13) > Red Globe grape/ raspberry (~0.095) and the absorptive (A t120 →B t120 ) and secretory (B t120 →A t120 ) P app (cm•s −1 × 10 −5 ) were Red Globe grape (1.20)> blackberry (0.06)/ raspberry (0.07) and Red Globe grape (1.55)/blackberry (1.38) > raspberry (0.98), respectively.…”
Section: Apparent Permeability Of Berry Polyphenolssupporting
confidence: 80%
“…During stage 1, a time-trend lineal reduction of TCD for Red Globe grape (R 2 = 0.91) but not for raspberry or blackberry was documented (Table S1 and Figure S1); this seems to be related to the lower amount and less diverse polyphenol profile (high catechin) in this table grape (Table 1), to higher electrochemical stability and apparent permeability and to a lower efflux of polyphenols (Table 2) than that observed for raspberry and blackberry. It is known, that anthocyanins>flavan-3-ols are pH-sensitive under simulated intestinal conditions [7,28], that anthocyanidins are more electroactive than their corresponding anthocyanins [24], that anthocyanin di-glycosides are more stable than mono-glycosides [21,22] and that GLUT-2 and SGLT-1 are efficient transporters for anthocyanins and flavan-3-ols at lower apical concentrations while P-gp/MCRP efflux systems are activated upon GLUT-2/SGLT-1 saturation [33,39,40].…”
Section: Dpvmentioning
confidence: 99%
See 1 more Smart Citation
“…The health benefits of these compounds depend on several factors including the ingested amount, molecular diversity, and gastrointestinal digestibility. For example, Jiao et al () demonstrated that in vitro simulated gastrointestinal digestion of blueberries significantly impact polyphenols and their antioxidant activity. In that study, the bioaccesibility of polyphenols was greatly decreased after intestinal digestion.…”
Section: Resultsmentioning
confidence: 99%
“…These differing pH conditions led to the changes in the content of various monomeric phenolic compounds. Jiao et al (2018) identified 31 individual polyphenols of blueberry polyphenols prior to and following in vitro simulated gastrointestinal digestion using HPLC-ESI-MS/MS. The results showed that some components were stable under the gastric digestion environment (such as delphinidin 3-O-arabinoside and dicaffeoylquinic acid), whereas others (such as peonidin 3-O-galactoside, petunidin 3-O-glucoside and malvidin 3-O-glucoside) could not be detected after digestion.…”
Section: Effects Of Simulated Digestion On the Phenolic Composition Omentioning
confidence: 99%